Effects of job stress on job performance and job satisfaction - Jehangir , Muhammad; Kareem, Nasir; Khan, Ayaz; Jan, Muhammad Tahir; Soherwardi, Shaheed (Institute of Interdisciplinary Business Research, 2011)
Job stress is increasingly becoming an epidemic in the work environment. Female Nursing staff is constantly encountering trouble, crisis and conflict in the work environment prevailing in the public sector hospitals that require them to cope with. The central theme of this research study is focused on digging out the fundamental causes of job stress of female nurses. Further, how job stress affects their job performance and job satisfaction. The study generated quantitative data which will open doors for further research in this area. This research study adopts quantitative approach using questionnaire methods. Several procedures were applied to carry out rigorous quantitative analysis. Organizations can help reduce the overall effects of job stress by developing and implementing prevention and intervention methods to help employees manage and cope with job stress. To reduce job stress of female nurses, this study suggests several measures along with employee’s assistance programe (EAP). This programme is focused on the employee’s total mental and physical condition. It was found that public sector hospitals are factories to manufacture stress. Female nurses experience more stress than male counterpart in the public sector hospitals. The findings of this paper revealed that job stress has negative co relation with job performance and job satisfaction.